Measuring Body Temperature Based Internet of Things (IoT) Using Esp8266 and Firebase - Indra Gunawan; Aris Sudianto; Muhamad Sadali (SISFOTENIKA, 2021)
Measuring the body temperature can be the basis for determining the health level of a person which increasing the body temperature can also be a reference to find out whether a person infection early symptoms of a disease, both fever and cases as currently occurring, namely as an indicator of determining whether someone is indicated to be infected with the Covid 19 virus, which is currently a pandemic in the various countries. Initially, measurement the body temperature was carried out massively using the body temperature measuring device circulating in the community using a thermometer that was already standardized by SNI, wherein the measurement process like this some obstacles or problems occur, which the officer being infected the risk  by virus covid19 and will cause  increasing in the cases. In this study, a tool was made to measure human body temperature based on the internet of things technology, which then the measurement data will be sent to an Android smartphone application based monitoring via the internet. This tool uses the MLX-90614 sensor device [1] to detect temperature, after that the data will be processed by Nodemcu ESP8266 and stored on the Firebase server before the data will sent to the user's monitor. The measurement result data will be displayed with the android application and if the temperature data exceeds the normal limit or> 37.50C, the system will send a sound signal alarm via a buzzer. The results of this study can achieve an accuracy level of about 95% from value of data the measuring temperature using device standards SNI and data display to the application monitoring need about 3 seconds.